TECTONIC CONTROL OF GABBRO COMPOSITION: RESULTS OF DISCRIMINANT ANALYSIS - Sholpo A.V.; Genshaft Yu.S. (My University, 1996)
The chemical compositions of gabbros from five different tectonic settings were subject to statistical analysis; the settings were flood basalts, ophiolites from mobile continental belts, and other mafic - ultramafic associations from fold belts, oceans, and island arcs. The discriminant analysis revealed five fields of data points representing gabbro compositions of five tectonic types defined by discriminant functions. The controlling factors were found to be the depth of magma generation, the primary lavas of gabbros, and the character of magma differentiation during the formation of tectonically controlled varieties. The resulting discriminant diagrams can be used for paleotectonic reconstructions in combination with other geological data.